The Influence of Media on Public Perception of Migration Issues: A Content Analysis - Ahmad Ismail; Fatima Hassan; Laila Mohamed (International Journal of Social Science and Humanity, 2024)
This article investigates how media coverage shapes public perception of migration issues, analyzing news reports, editorials, and social media content. By focusing on themes of security, economy, and humanitarian concerns, the study evaluates the role of media in influencing opinions and policy debates on migration. Findings indicate that media framing can significantly sway public attitudes, highlighting the need for balanced reporting.